High‐throughput measurement of recombination rates and genetic interference in Saccharomyces cerevisiae. Issue 6 (30th April 2018) - Raffoux, Xavier; Bourge, Mickael; Dumas, Fabrice; Martin, Olivier C.; Falque, Matthieu
Abstract: Allelic recombination owing to meiotic crossovers is a major driver of genome evolution, as well as a key player for the selection of high‐performing genotypes in economically important species. Therefore, we developed a high‐throughput and low‐cost method to measure recombination rates and crossover patterning (including interference) in large populations of the budding yeast Saccharomyces cerevisiae . Recombination and interference were analysed by flow cytometry, which allows time‐consuming steps such as tetrad microdissection or spore growth to be avoided. Moreover, our method can also be used to compare recombination in wild‐type vs. mutant individuals or in different environmental conditions, even if the changes in recombination rates are small. Furthermore, meiotic mutants often present recombination and/or pairing defects affecting spore viability but our method does not involve growth steps and thus avoids filtering out non‐viable spores.